FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KONSUMEN BERAS ORGANIK DI KOTA DENPASAR - Tisnawati, Ni Made (PIRAMIDA, 2015)
One of the main challenges of the demographic bonus in Indonesia is still low quality of food. One example of food quality and ensuring environmental sustainability are organic rice. Organic rice excellence not only ensure the preservation of the environment, but also a positive effect for the health of the consumer. This study was conducted to identify the factors that influence consumer demand for organic rice, especially in the city of Denpasar. This is done in order to determine the segmentation of consumers, as well as increasing consumer interest in consuming organic rice, as an effort to support the sustainability of organic farming in the province of Bali, and to improve the quality of human resources in the long term. To achieve the objectives of the study, used a quantitative approach (the factor analysis, non-parametric analysis) and a qualitative approach. Results of the analysis of data processing techniques explanatory factor analysis shows there are two factors that affect consumer demand for the product and its benefits, as well as social factors consumers.
Keywords: demand; consumers; organic rice